Selected papers from the 12th international symposium on electromagnetic fields in electrical engineering 2005, Volume 25, Issue 3. - Krawczk, Professor Andrzej (COMPEL: The International Journal for Computation and Mathematics in Electrical and Electronic Engineering., 2006)
This e-book is devoted to the papers that were presented at the International Symposium on Electromagnetic Fields in Electrical Engineering ISEF'05 and is guest edited by Professor S. Wiak of the University of Lodz. The papers cover the subject areas of computational electromagnetics, electromagnetic engineering, coupled field and special applications, micro- and special devices, bioelectromagnetics and electromagnetic hazards, and magnetic material modeling.